PENGARUH BEBERAPA KONSENTRASI EKSTRAK AKAR TUBA (Derris Elliptica Roxb.) TERHADAP SERANGAN HAMA WALANG SANGIT (LEPTOCORISA ACUTA THUNBERG) (Hemptera :Alydidae) PADA TANAMAN PADI (Oryza Sativa L.) - Humaya, Humaya; Nurkhasanah, Nurkhasanah; Pasaru, Flora (AGROTEKBIS, 2018)
The study aims to determine the effect several of tuba root extract concentrationson the intensity of the attacks walang rice pest (Leptocorisa acuta) and rice production. This research was conducted in the village of Wosu, District Bungku West, Morowali District, in December 2015 to March 2016. The study used an experimental trial designs using completely randomized design (CRD) with tuba root extract consists of 5 treatments and 3 repetitions, which consists of tuba root extract concentration without any concentration treatment (control), the concentration of 1%, 2%, 3%, and 4% / liter water / plot, after it were applied to each plot observations already prepared. The spraying was done three times i.e. at the age of 62 days, aged 76 and 90 days. Interfal observations carried out at walang sangit intensity of attacks carried out on every 3 days after application. Based on the analysis HSD test the level of 5%, indicating that the treatment of several concentrations of tuba root extract can affect the intensity and reduce the level of L. acuta attack, whereas the concentration of tuba root extract with a concentration of  4% / liter water / plot can suppress the attack L. acuta and increase rice production by 95%.